THE EFFECT WORKING ENVIRONMENT, JOB CHARACTERISTIC AND JOB MOTIVATION TO JOB SATISFACTION AT LECTURE JAMBI UNIVERSITAS - Rosmiati Rosmiati; Ekawarna Ekawarna; Eddy Haryanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
The objective of this research is to obtain information on the effect of working environment, job Characteristic and job motivation to job satisfaction. The population of this research is the Lecture Jambi University. The total number of the research sample was 273 Official Member of Lecture Jambi University and they were taken randomly. Data analysis technique was used path analisys with SPSS and LISREL program.The formulation of this research are: 1) Is the work environment (X1) directly influence the work motivation (X3),2) Is the work environment (X1) directly influence job satisfaction (Y), 3) Is the Job Characteristics (X2) directly influence the work motivation (X3), 4) Is the Job Characteristics (X2) directly influence job satisfaction (Y), 5) Is the work motivation (X3) directly influence job satisfaction (Y) 6). Is the work environment (X1) indirect effect on job satisfaction (Y) but the first direct effect on work motivation (X3) 7). Is the Job Characteristics (X2) indirect effect on job satisfaction (Y) but the first direct effect on work motivation (X3).Based on the above formula, it can be presumed that that job satisfaction can be explained by the variable work motivation, job characteristics, and work environment.Keywords : working environment, job characteristic And job motivation to job satisfaction